Digitalisasi Kehidupan Keluarga dan Implikasinya Terhadap Reformulasi Hukum Keluarga Islam - Riadi, Holan (LP3M STITNU AL HIKMAH MOJOKERTO, 2025)
The development of digital technology has brought significant changes to various aspects of human life, including the dynamics of family relationships. Digitalization not only affects communication patterns among family members but also transforms the structure of economic role distribution, decision-making processes within households, and the way individuals build social relationships within the family. These transformations have generated new legal challenges that require reinterpretation of Islamic family law concepts in order to remain relevant to contemporary social realities. This article aims to analyze the influence of the digitalization of family life on changes in family relational structures and its implications for the need to reformulate Islamic family law. This study employs a qualitative method using normative and conceptual approaches through a literature review of classical and contemporary works related to Islamic family law, maqashid al-shari’ah, and the dynamics of social transformation in modern society. The findings indicate that digitalization has altered authority relations within families, patterns of financial responsibility, and communication mechanisms among family members. These changes necessitate the reinterpretation of several key concepts in Islamic family law, such as family leadership (qiw?mah), the distribution of economic roles between husband and wife, and moral responsibilities in maintaining family harmony in the digital era. Therefore, the reformulation of Islamic family law should be carried out through the maqashid al-shari’ah approach in order to ensure that Islamic law remains capable of addressing contemporary challenges while preserving the fundamental values of the sharia aimed at promoting the welfare of families and society.